HEALTHCARE REFORM OF UKRAINE: MECHANISM AND MANAGEMENT TOOLS - Kinash, Iryna Petrivna; Savchuk, Lilia (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
The article is aimed at presenting the economic mechanism and tools for the development of health care in Ukraine in terms of reforming the industry. It has been found that the state of health of citizens in Ukraine has been alarming for a long time. This is evidenced by the fact that the average life expectancy of Ukrainians is only 72 years, which is 11 years less than in most developed countries. This condition is due to many factors, including inefficient development mechanism. It is revealed that the introduction of medical reform is a serious challenge today. An economic mechanism for ensuring health care reform in Ukraine and development tools have been proposed. The following tools are presented and substantiated: targeted development programs; targeted taxation; targeted use of the tax; outsourcing; preferential pricing and lending for development programs and projects; incentives for health workers and hospitals; Medical Insurance; reimbursement; support for the private sector and the development of public-private partnerships. The proposed tools are aimed at improving the management system of health care, in order to optimize the use of resources, balance the interests of businesses, society and the state. It is noted that these tools must meet certain requirements, in particular: to operate within the existing regulatory framework; to provide protection of the population in providing guarantees of medical services; provide an opportunity to predict and timely prevent adverse development processes; enable effective functioning; have a clear structure of delimitation of authorities. The effectiveness of economic instruments will be achieved through close interaction and interaction with organizational tools. It is concluded that the complex combination of methods and proposed tools in the economic mechanism will provide a synergistic effect in the direction of achieving the indicators envisaged by the reform.